Review on the Macedonian Wedding Singing - Velichkovska, Rodna (Ethnographica et Folkloristica Carpathica, 2025)
The wedding as a rite of passage in Macedonia is a living tradition that preserves numerous and various evidence either on the social relations of the traditional community or the changes of this complex family-customs and ritual cycle. The characteristic of this complex is that it abounds with many ritual-magical actions, the basis of which is the apotropaic character. The most significant signs, according to which it is possible to determine the boundaries of the local singing style, include: the constancy of the traditional wedding scenario, the commonality of the wedding repertoire and the types of musical-poetic structures. Remains of the former characteristics of social life are deposited in the entire wedding complex: the former rights and duties of the woman and her position in the village community, as well as the old beliefs of magical and religious character. The main characters in the wedding ceremony, apart from the bride and the groom, are: the father-in-law, the mother-in-law, the best man, the groomsman, the bride’s brother, the brother-in-law and other participants, who are called wedding guests or in-laws. For them, during the entire wedding ritual, songs are sung, related to the entire ritual process and have a precisely determined ritual place and performance time. Their performance is related to four time-space segments of the wedding.